2019
DOI: 10.1098/rsta.2018.0148
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the scales in numerical weather and climate predictions: will exascale be the rescue?

Abstract: We discuss scientific features and computational performance of kilometre-scale global weather and climate simulations, considering the Icosahedral Non-hydrostatic (ICON) model and the Integrated Forecast System (IFS). Scalability measurements and a performance modelling approach are used to derive performance estimates for these models on upcoming exascale supercomputers. This is complemented by preliminary analyses of the model data that illustrate the importance of high-resolution models to gain imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 30 publications
0
77
0
Order By: Relevance
“…Table 1 of Schulthess et al 2019) and a horizontal grid spacing of 1 km on the currently largest supercomputer available would fall short of the 1 SYPD target by approximately a factor of 20 . A recent study by Neumann et al (2019) reports a shortfall of a factor of 30, extrapolating results from the ICON model at 5 km grid spacing and assuming perfect weak scaling.…”
Section: E579mentioning
confidence: 79%
See 2 more Smart Citations
“…Table 1 of Schulthess et al 2019) and a horizontal grid spacing of 1 km on the currently largest supercomputer available would fall short of the 1 SYPD target by approximately a factor of 20 . A recent study by Neumann et al (2019) reports a shortfall of a factor of 30, extrapolating results from the ICON model at 5 km grid spacing and assuming perfect weak scaling.…”
Section: E579mentioning
confidence: 79%
“…However, what resolution will actually be needed for the later purpose is not yet fully understood. On the one hand, convective cloud processes (dynamics, turbulence, and microphysics) occur on scales that are not fully resolved at kilometer resolution (Skamarock 2004;Neumann et al 2019;Panosetti et al 2019b). On the other hand, studies have indicated that there is some bulk convergence at grid resolutions around 2 km, that is, the feedbacks between convective clouds and the larger-scale flow are partly captured at resolutions at which the structural details of the cloud field are not yet fully resolved (Langhans et al 2012;Harvey et al 2017;Ito et al 2017;Panosetti et al 2019Panosetti et al , 2020.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known from earlier studies that SST features on these scales are important to simulate the structure and movement of cyclones (e.g., [76,77]), their deepening rate (e.g., [78,79]), and maybe even the frequency of lightning [80,81]. Nevertheless, the computational challenge of scaling up these results (weather) to long global simulations (climate), or ensemble of these, is very significant [82,83] and only begins to be addressed in atmosphere-only set-ups (e.g., [84]).…”
Section: Small-scale Oceanic Forcingmentioning
confidence: 99%
“…In recent years, studies have demonstrated the added value of explicitly resolved convection also for the simulation of precipitation in climate simulations (e.g., Hohenegger et al 2008;Kendon et al 2014;Ban et al 2014;Leutwyler et al 2017). Recent advances in computing power and architecture made it possible to increase the domain size and integration time allowing for decade-long continentalscale climate simulations at convection-resolving resolution (e.g., Leutwyler et al 2016;Prein et al 2017;Hentgen et al 2019) and even global-scale convection-resolving simulations have been conducted over week-long periods (e.g., Miyamoto et al 2013;Bretherton and Khairoutdinov 2015;Fuhrer et al 2018;Neumann et al 2019).…”
Section: Introductionmentioning
confidence: 99%